Teleworking and Workload Balance on Job Satisfaction: Indonesian Public Sector Workers During Covid-19 Pandemic - Khusnul Rofida Novianti; Kenny Roz (APMBA (Asia Pacific Management and Business Application), 2020)
The unexpected condition caused by coronavirus disease (Covid-19) in late December 2019 that spread all over the world has changed the human resource workforce. One of the Indonesian government decisions to reduce the infection is home base teleworking (working from home) policies for mostly all sectors in Indonesia, one of them is the public sector. This new work style that has never been experienced before may cause psychological stress of workload and affect satisfaction. This research aims to measure the effects of teleworking on job satisfaction mediated by the workload in 168 public sector workers all over Indonesia. Data obtained using an online questionnaire from February – March 2020 and analyzed use Smart-PLS software. The result showed that teleworking has a significant effect on the workload, but not significant effect on job satisfaction. Workload has a negative and not significant effect on job satisfaction. Hence, the workload is not the best predictor for mediating the effect of teleworking and  job satisfaction. Workers in the public sector feeling more stressed during teleworking and it caused their job satisfaction to decrease. This kind of situation can be a sign for the decision-maker on how to improve their worker's job satisfaction during the teleworking.